STUDI PAKAN ALAMI DAN PERILAKU MAKAN BEKANTAN (Nasalis larvatus wurmb.) DI KAWASAN KONSESI PT. PERTAMINA EP ASSET 5 SANGASANGA KABUPATEN KUTAI KERTANEGARA, KALIMANTAN TIMUR - Hendra, Medi (Program Studi Biologi FMIPA Universitas Mataram, 2015)
The forest areas in Delta Mahakam were decreasing annually and it has been impact directly to wildlife which used these forests as food sources and live on it. One of those species is proboscis monkey (Nasalis larvatus Wurmb.), a rare and endemic species of Kalimantan. Research on feeding behavior and ecological can be used in the effort to habitat preservation and protection of proboscis monkey in that area. The aims of this study was to determine the natural feeding plants which used and the feeding behavior by proboscis monkey (N. larvatus Wurmb.) along Kutai Lama Dalam River, Tanjung Una and Muara Sanga-sanga on Kutai Kartanegara regency, East Kalimantan. The research was conducted in June to July 2014. The method used in this study was direct observation, data collection, sampling, herbarium preparation and identification of herbarium plant species. Observations carried out 2 times a day at 08:00 to 10:00am and 16:00 to 18:00pm for 30 days observation. The results was obtained 18 plants of species categorized as natural feeding plants of proboscis monkeys, 6 of them is the main feed (Ficus benjamina L., Sonneratia caseolaris L. Syzygium grande Wight. Gluta rengas L., Gluta wallicii Hook. and Heritiera ellata Ridl), and the rest of them was a food supplement. The Ficus benjamin L. has the highest percentage of feeding sources (44, 8%), whereas the leaves (95,64 %) was the highest part to consumed. The feeding behavior of proboscis monkey along river in Kutai Lama Dalam generally start with foraging activity, and later was the activity of taking and putting food into the mouth. The difference in feeding behavior was showed based on the type of plants consumed by the proboscis monkey.Â Key words:Â Natural plant feed, plant identification, proboscisÂ monkey (Nasalis larvatus Wurmb.), Delta Mahakam